The (im)possibilities of open data?. Issue 5 (4th July 2019) - Jamieson, David; Wilson, Rob; Martin, Mike
ABSTRACT: The perceived benefits and possibilities that the production, publication and consumption of Open Government Data (OGD) can provide to citizens and the economy are well documented. In the UK, this has resulted in the introduction of key legislation, such as the Freedom of Information Act 2010, and the Data Protection Act 2018. However, there is insufficient empirical knowledge and evidence to support the extent as to which the intended possibilities of OGD (transparency, releasing social and commercial value, and participation and engagement) have been realized. This article investigates these supposed possibilities and suggests that they may be impossibilities instead. IMPACT: Open government data has long been widely heralded as a mechanism to underpin policy-making, improve citizen engagement, and stimulate innovation. Despite the wealth of literature disputing these aspects individually, this article challenges the perceived benefits collectively against a backdrop of changing political climate and policy. The authors challenge three perceived benefits surrounding the production, consumption and publication of open government data and provide additional considerations that can be made to increase the efficiency and impact of open government data.